Calvin's New Testament commentaries ; vol. 12 - Calvin, John, 1509-1564; Johnston, W.B.; Torrance, David W.; Torrance, Thomas Forsyth, 1913- (Grand Rapids, MI Eerdmans, 1963)
Contents : v. 12 : The epistle of Paul the Apostle to the Hebrews and the First and Second epistles of St Peter. Includes bibliographical references and indexes.
Keywords: Bible. N.T. Hebrews -- commentaries; Bible. N.T. Peter -- commentaries